Monetization of IoT data using smart contracts. Issue 1 (1st January 2019) - Suliman, Ahmed; Husain, Zainab; Abououf, Menatallah; Alblooshi, Mansoor; Salah, Khaled
Abstract : In the era of the Internet of Things (IoT), smart connected devices have the ability to generate data that could be of interest to the public. This paves the way for an emerging market for monetized data exchanges, where IoT device owners can sell access to live data generated by their connected devices to interested users. Implementing a trusted, cost‐efficient, automatic monetization solution of IoT data can be a challenging problem and usually involves intermediaries and centralised governance and management. Blockchain and smart contracts introduce a secure and trusted platform to carry out transactions in a highly trusted, secure, decentralised manner. In this study, they present a blockchain‐solution and implementation using Ethereum smart contracts for monetizing IoT data with automated payment involving no intermediary. The authors discuss key aspects related to architectural design, entity relations, interactions among participants, logic flow, implementation and testing of the overall system functionality.